Ice ages and butterflyfishes: Phylogenomics elucidates the ecological and evolutionary history of reef fishes in an endemism hotspot. Issue 22 (23rd October 2018) - DiBattista, Joseph D.; Alfaro, Michael E.; Sorenson, Laurie; Choat, John H.; Hobbs, Jean‐Paul A.; Sinclair‐Taylor, Tane H.; Rocha, Luiz A.; Chang, Jonathan; Luiz, Osmar J.; Cowman, Peter F.; Friedman, Matt; Berumen, Michael L.
Abstract: For tropical marine species, hotspots of endemism occur in peripheral areas furthest from the center of diversity, but the evolutionary processes that lead to their origin remain elusive. We test several hypotheses related to the evolution of peripheral endemics by sequencing ultraconserved element (UCE) loci to produce a genome‐scale phylogeny of 47 butterflyfish species (family Chaetodontidae) that includes all shallow water butterflyfish from the coastal waters of the Arabian Peninsula (i.e., Red Sea to Arabian Gulf) and their close relatives. Bayesian tree building methods produced a well‐resolved phylogeny that elucidated the origins of butterflyfishes in this hotspots of endemism. We show that UCEs, often used to resolve deep evolutionary relationships, represent an important tool to assess the mechanisms underlying recently diverged taxa. Our analyses indicate that unique environmental conditions in the coastal waters of the Arabian Peninsula probably contributed to the formation of endemic butterflyfishes. Older endemic species are also associated with narrow versus broad depth ranges, suggesting that adaptation to deeper coral reefs in this region occurred only recently (<1.75 Ma). Even though deep reef environments were drastically reduced during the extreme low sea level stands of glacial ages, shallow reefs persisted, and as such there was no evidence supporting mass extirpation of fauna in this region. Abstract : We test several hypotheses related to the evolution of peripheral endemics by sequencing ultraconserved element loci to produce a genome‐scale phylogeny of 47 butterflyfish species (family Chaetodontidae), including all shallow‐water butterflyfish from the Red Sea to Arabian Gulf. Our analyses indicate that unique environmental conditions in the coastal waters of the Arabian Peninsula probably contributed to the formation of endemic butterflyfishes. Older endemic species are also associated with narrow versus broad depth ranges, suggesting that adaptation to deeper coral reefs in the coastal waters of the Arabian Peninsula occurred only recently (<1.75 Ma).